The Pitfalls of Visual Representations: A Review and Classification of Common Errors Made While Designing and Interpreting Visualizations. (14th October 2015) - Bresciani, Sabrina; Eppler, Martin J.
A large body of research has addressed the benefits of visualization, whereas the analysis of the pitfalls has not received systematic attention. We aim to provide an overview of the common pitfalls and potential disadvantages of visual representations based on a multidisciplinary literature review. Subsequently, we develop a theoretically grounded classification of common cognitive, emotional, and social risks of visualization and populate it with a comprehensive list of visualization pitfalls. The aim of this research is not to diminish the potential of visualization, but rather to improve visual literacy by structuring our understanding of the possible limitations of graphic representations.